High-strength all-light concrete as well as preparation method and application thereof
By using additives such as hydroxypropyl cellulose and modified ligno fibers in lightweight concrete, the problems of low strength and easy separation of lightweight concrete are solved, and a fully light concrete with high strength and good flow is achieved, suitable for High-rise building.
Patent Information
- Application Number
- CN202411062969.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-05
AI Technical Summary
The existing lightweight concrete has a low strength, which leads to a limited range of use, and is prone to problems of layered isolation and slump reduction during the stirring process.
Using hydroxypropyl cellulose as a modifier, combined with modified ligno fibers and silica sol, the modified ligno fibers are treated with branch grafts and initiators to form better dispersion and stability, increasing the secondary cement Hydration reaction improves the strength and compactness of concrete.
High-strength fully light concrete is achieved, ensuring good flowability and working performance, solving the problems of low strength and easy separation of light concrete, achieving LC60 strength grade, and reducing the weight of high-rise buildings.
Smart Images

Figure BDA0004978526270000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a high-strength all-light concrete and a preparation method and application thereof. Background Art
[0002] Modern civil engineering has put forward new requirements on the quality, energy efficiency and fire safety of structural components. Lightweight concrete has become one of the important solutions in response to these demands. Compared with ordinary concrete, the basic characteristics of lightweight concrete include lower bulk density and better thermal insulation performance. Therefore, it is not only regarded as a building material, but also widely used as thermal insulation material and aesthetic building finishes. From the perspective of earthquake resistance, lightweight aggregate concrete has significant advantages due to its low deadweight. In addition, lightweight aggregates are usually expansive materials and are therefore very effective in sound insulation and thermal insulation. By replacing ordinary concrete with lightweight aggregate concrete in part or in its entirety, the dead load of the structure can be greatly reduced, which brings considerable benefits. There is still a major problem in the application of lightweight aggregate concrete in our country's engineering, that is, the low strength of lightweight aggregate concrete. The existing lightweight concrete has low strength. The strength grade of lightweight aggregate concrete currently used is mainly concentrated below LC40, which limits its scope of use. At the same time, its workability during the application process is poor, mainly because the dry expanded clay causes the slump of the concrete mixture to decrease after absorbing water. The greater the water absorption rate, the greater the slump loss. In addition, due to the large difference in density between expanded clay and cement mortar, expanded clay concrete is prone to stratification and segregation during the mixing process. Therefore, expanded clay concrete is prone to stratification and segregation, and has a large slump loss. In addition, under the action of pressure, lightweight aggregate is prone to absorbing moisture in the concrete. Multiple factors lead to the problem of pump blockage when pumping expanded clay concrete.
[0003] Therefore, it is imperative to provide a fully lightweight concrete with good homogeneity and high strength. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a high-strength all-light concrete that improves the homogeneity of lightweight concrete, ensures good working performance and high strength with high fluidity. The concrete has a slump of ≥240mm, an expansion of ≥550mm, good working performance, reaches the LC60 strength grade, and solves the problems of poor homogeneity and low strength of all-light concrete.
[0005] The present invention also provides a method for preparing the high-strength all-light concrete.
[0006] The present invention also proposes the application of the high-strength all-light concrete in high-rise buildings.
[0007] According to a first aspect of the present invention, a high-strength all-light concrete is proposed. The raw materials for preparing the concrete include, by weight, 500-540 parts of cement, 90-110 parts of mineral powder, 50-60 parts of fly ash, 400-500 parts of pottery sand, 350-380 parts of shale ceramsite and 60-70 parts of hydroxypropyl cellulose.
[0008] The embodiments according to the first aspect of the present invention have at least the following beneficial effects:
[0009] In the present invention, hydroxypropyl cellulose is added as a modifier when preparing high-strength all-light concrete, which solves the problem of lightweight aggregate floating when preparing LC60 high-strength all-light concrete, and at the same time achieves light weight and high strength, solves the problem of low fluidity of high-strength all-light concrete, and the obtained strong all-light concrete has good working performance, reduces the deadweight of high-rise buildings, and can better resist the influence caused by swaying;
[0010] In some embodiments of the invention, the cement comprises P.O42.5 grade cement.
[0011] In some embodiments of the present invention, the mineral powder includes S95 grade mineral powder.
[0012] In some embodiments of the present invention, the fly ash comprises Class II fly ash.
[0013] In some embodiments of the present invention, the apparent density of the ceramic sand is 920 kg / m 3 The bulk density of the ceramic sand is 523kg / m 3 The compound fineness of the ceramic sand is 2.5 to 3.1.
[0014] In some embodiments of the present invention, the apparent density of the shale ceramsite is 1090 kg / m 3 .
[0015] In some embodiments of the present invention, the bulk density of the shale ceramsite is 698 kg / m 3 .
[0016] The coarse aggregate in the present invention is crushed stone type shale ceramsite, and the fine aggregate is pottery sand, which solves the problem that the all-light concrete has poor workability and is not easy to pump, that is, the present invention obtains an HPMC-added pumpable LC60 high-strength all-light concrete.
[0017] In some embodiments of the present invention, the porosity of the shale ceramsite is 31%.
[0018] In some embodiments of the present invention, the cylinder compressive strength of the shale ceramsite is 6.2 MPa.
[0019] In some embodiments of the present invention, the shale ceramsite has a 1h water absorption rate of 16.2%.
[0020] In some embodiments of the present invention, the particle size of the shale ceramsite is 5 to 16 mm.
[0021] In some embodiments of the present invention, the raw materials for preparing the high-strength all-light concrete further include: polycarboxylate water-reducing agent;
[0022] The water reduction rate of the carboxylic acid water reducer is 25-28%.
[0023] In some embodiments of the present invention, the raw materials for preparing the high-strength all-light concrete also include water.
[0024] In some embodiments of the present invention, the raw materials for preparing the high-strength all-light concrete further include: aminosulfonate, modified wood fiber and silica sol;
[0025] The raw materials for preparing the modified wood fiber include wood fiber, a grafting agent and an initiator.
[0026] In the present invention, the introduction of the grafting agent makes the surface of the wood fiber more hydrophilic, thereby enhancing its compatibility with water-based liquids (such as concrete slurry) and improving the adhesion between the wood fiber and the concrete matrix: the wood fiber treated with grafting polymerization has better dispersibility and stability in concrete, can effectively reduce shrinkage cracks of concrete, and improve tensile strength and durability.
[0027] Wood fibers, through their natural fiber structure, form air bubbles in the concrete and provide structural support.
[0028] On the one hand, the carboxyl group (-COOH) on the modified wood fiber reacts with the amino group in the aminosulfonate surfactant to form an amide bond, which helps to firmly adsorb the surfactant molecules on the surface of the wood fiber to form a molecular film, which can reduce the pore size of the bubbles in the liquid and make the bubbles more stable. In concrete, it helps to reduce the pore size of the pores in the concrete, reduce the porosity in the concrete, improve the density and impermeability of the concrete, and improve the uniformity, density and durability of the concrete. On the other hand, the surface of the modified wood fiber has amino functional groups, which provide active sites to react with Ca in the cement hydration products. 2+ Ionic bonding helps promote the secondary hydration reaction of cement, which in turn promotes the hardening and strength of concrete.
[0029] Silica sol may form a silicon-oxygen cluster structure on the surface of modified wood fiber. These clusters may be combined with the surface of wood fiber through chemical bonds to form a protective layer of silicon-oxygen clusters. It can play the following roles: 1. It helps to prevent the decomposition and destruction of wood fiber in concrete, and improve its stability and durability in concrete; 2. The silicon-oxygen clusters combine with silicates on the surface of cement particles to increase the dispersibility of cement particles and promote the contact between cement particles and water; 3. The interaction between silica sol and the surface of cement particles helps to promote the secondary hydration reaction of cement and release metal ions, such as calcium ions (Ca 2+ ), chemically react with the hydrates in cement, such as calcium ions forming more CSH gel with silicates and water in cement. This helps to enhance the mechanical properties and durability of cement and improve the overall performance of concrete.
[0030] Silica sol may form a silica cluster structure on the surface of modified wood fiber. These silica clusters may combine with silicates on the surface of cement particles, increase the dispersibility of cement particles, promote the contact between cement particles and water, and thus promote the secondary hydration reaction of cement. The reaction products may contain metal ions, such as calcium ions (Ca2+), aluminum ions (Al3+), etc. These metal ions may chemically react with the hydrates in cement to promote the secondary hydration reaction of cement. When calcium ions react with silicates and water in cement, the generated CSH gel increases. CSH gel is one of the main components of cement hydration products, and it plays a key role in the cement hardening process. Therefore, the addition of calcium ions may promote the formation of more CSH gel, which can enhance the mechanical properties and durability of cement-based materials.
[0031] In some embodiments of the present invention, the aminosulfonate comprises at least one of sodium aminosulfonate and potassium aminosulfonate.
[0032] In some embodiments of the present invention, the silica sol comprises a nano-scale silica sol aqueous solution, and the particle size of the silica sol is 10-30 nm.
[0033] In some embodiments of the present invention, the grafting agent includes at least one of methacrylic acid, acrylic acid, acryloyl chloride, vinylacyl chloride silane and acrylamide.
[0034] In some embodiments of the present invention, the initiator includes at least one of ammonium persulfate and potassium persulfate.
[0035] According to a second aspect of the present invention, a method for preparing high-strength all-light concrete is provided, comprising the following steps: mixing raw materials for preparing the high-strength all-light concrete, stirring and then pouring.
[0036] In some embodiments of the present invention, the method for preparing the modified wood fiber comprises: mixing and reacting the wood fiber, the grafting agent and the initiator.
[0037] According to a third aspect of the present invention, an application of the high-strength all-light concrete in high-rise buildings is proposed. DETAILED DESCRIPTION
[0038] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0039] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0041] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0042] The raw materials used in the following implementation cases are as follows:
[0043] The cement is P.O42.5 cement produced by Hunan Conch Cement Co., Ltd., with a density of 3.10g / cm3, a specific surface area of 315m2 / kg, and a 28-day strength of 48.6Mpa;
[0044] The mineral powder is S95 grade mineral powder produced by Hunan Helong Building Materials Co., Ltd., with a 28-day activity index of 105%, a density of 2.91g / cm3, and a specific surface area of 425m2 / kg;
[0045] The fly ash was Grade II fly ash produced by Yiyang Xingtai Building Materials Co., Ltd., with a fineness of 19%, a water requirement ratio of 96%, and a 28-day activity index of 76%;
[0046] The admixture is a high-performance polycarboxylate water-reducing agent from Sika (China) Co., Ltd., with a solid content of 24.8% and a water reduction rate of 26.7%;
[0047] The water is tap water;
[0048] The apparent density of coarse aggregate shale ceramsite is 1090kg / m3, the bulk density is 698kg / m3, the porosity is 31%, the cylinder pressure strength is 6.2Mpa, the 1h water absorption rate is 16.2%, and the particle size is 5-16mm; the apparent density is 920kg / m3, the bulk density is 523kg / m3, the compound fineness is 2.5-3.1, continuous pole matching, and the particle shape is good.
[0049] Example 1
[0050] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0051] A high-strength all-light concrete is prepared by the following raw materials: according to the mass of raw materials required for each cubic meter of concrete: 540kg of cement, 100kg of mineral powder, 55kg of fly ash, 360kg of shale ceramsite, 82kg of water, 68kg of 3.5‰ HPMC solution, and 21.5kg of admixture.
[0052] A method for preparing high-strength all-light concrete, the specific steps are:
[0053] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0054] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0055] S3: slowly add water and continue stirring for 3 hours to ensure that the various components in the mixture are fully mixed and reacted to obtain a slurry;
[0056] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0057] Example 2
[0058] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0059] A high-strength all-light concrete is prepared by the following raw materials: according to the mass of raw materials required for each cubic meter of concrete: 530kg of cement, 100kg of mineral powder, 50kg of fly ash, 460kg of shale ceramsite, 82kg of water, 68kg of 3.5‰ HPMC solution, and 21.5kg of admixture.
[0060] A method for preparing high-strength all-light concrete, the specific steps are:
[0061] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0062] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0063] S3: slowly add water and continue stirring for 3 hours to ensure that the various components in the mixture are fully mixed and reacted to obtain a slurry;
[0065] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0066] Example 3
[0067] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0068] A high-strength all-light concrete is prepared by the following raw materials: 500kg of cement, 110kg of mineral powder, 55kg of fly ash, 360kg of shale ceramsite, 82kg of water, 68kg of 3.5‰ HPMC solution, and 21.5kg of admixture according to the mass of raw materials required for each cubic meter of concrete.
[0069] A method for preparing high-strength all-light concrete, the specific steps are:
[0070] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0071] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0072] S3: slowly add water and continue stirring for 3 hours to ensure that the various components in the mixture are fully mixed and reacted to obtain a slurry;
[0074] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0075] Example 4
[0076] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0077] A high-strength all-light concrete is prepared from the following raw materials: 500kg of cement, 110kg of mineral powder, 55kg of fly ash, 500kg of shale ceramsite, 82kg of water, 68kg of 3.5‰ HPMC solution, and 21.5kg of admixture per cubic meter of concrete.
[0078] A method for preparing high-strength all-light concrete, the specific steps are:
[0079] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0080] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0081] S3: slowly add water and continue stirring for 3 hours to ensure that the various components in the mixture are fully mixed and reacted to obtain a slurry;
[0083] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0084] Example 5
[0085] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0086] A high-strength all-light concrete is prepared by the following raw materials: according to the mass of raw materials required for each cubic meter of concrete: 500 kg of cement, 110 kg of mineral powder, 55 kg of fly ash, 360 kg of shale ceramsite, 82 kg of water, 68 kg of 3.5‰ HPMC solution, 21.5 kg of admixture, 0.2 kg of aminosulfonate, 1.5 kg of modified wood fiber, and 1 kg of silica sol.
[0087] A method for preparing high-strength all-light concrete, the specific steps are:
[0088] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0089] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0090] S3: slowly add water, aminosulfonate, modified wood fiber and silica sol, and continue stirring for 3 hours to ensure that the various components in the mixture are fully mixed and reacted to obtain a slurry;
[0091] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0092] The preparation method of modified wood fiber is as follows:
[0093] A1: Wash and dry the wood fiber;
[0094] A2: Place the dried wood fiber in a reaction container, add initiator ammonium persulfate (APS), inject methacrylic acid solution into the reaction container to ensure that the wood fiber is completely soaked, and perform polymerization reaction at 80° C. to obtain modified wood fiber.
[0095] Example 6
[0096] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0097] A high-strength all-light concrete is prepared by the following raw materials: according to the mass of raw materials required for each cubic meter of concrete: 500 kg of cement, 110 kg of mineral powder, 55 kg of fly ash, 360 kg of shale ceramsite, 82 kg of water, 68 kg of 3.5‰ HPMC solution, 21.5 kg of admixture, 0.2 kg of sodium aminosulfonate, 1.5 kg of modified wood fiber, and 1 kg of silica sol.
[0098] A method for preparing high-strength all-light concrete, the specific steps are:
[0099] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0100] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0101] S3: Slowly add water, aminosulfonate, modified wood fiber and silica sol, and continue stirring for 3 hours to ensure that the mixture is
[0102] The various components in the mixture are fully mixed and reacted to obtain a slurry;
[0103] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0104] The preparation method of modified wood fiber is as follows:
[0105] A1: Wash and dry the wood fiber;
[0106] A2: Place the dried wood fiber in a reaction container, add initiator ammonium persulfate (APS), inject acrylic acid solution into the reaction container to ensure that the wood fiber is completely soaked, and perform polymerization reaction at 80°C to obtain modified wood fiber.
[0107] Example 7
[0108] This embodiment provides high-strength all-light concrete and a preparation method thereof, specifically:
[0109] A high-strength all-light concrete is prepared by the following raw materials: according to the mass of raw materials required for each cubic meter of concrete: 500 kg of cement, 110 kg of mineral powder, 55 kg of fly ash, 360 kg of shale ceramsite, 82 kg of water, 68 kg of 3.5‰ HPMC solution, 21.5 kg of admixture, 0.2 kg of aminosulfonate, 1.5 kg of modified wood fiber, and 1 kg of silica sol.
[0110] A method for preparing high-strength all-light concrete, the specific steps are:
[0111] S1: Mix cement, mineral powder, fly ash and shale ceramsite in proportion to form a mixture;
[0112] S2: Gradually add HPMC solution and admixtures to the mixture and stir until the mixture is uniform;
[0113] S3: Slowly add water, sodium sulfamate, modified wood fiber and silica sol, and continue stirring for 3 hours to ensure that the mixture is
[0114] The various components in the mixture are fully mixed and reacted to obtain a slurry;
[0115] S4: Pour the mixed slurry into the mold, and perform compaction and curing.
[0116] The preparation method of modified wood fiber is as follows:
[0117] A1: Wash and dry the wood fiber;
[0118] A2: Place the dried wood fiber in a reaction container, add initiator ammonium persulfate (APS), inject acrylic acid solution into the reaction container to ensure that the wood fiber is completely soaked, and perform polymerization reaction at 80°C to obtain modified wood fiber.
[0119] Comparative Example 1
[0120] This comparative example provides a high-strength all-light concrete. The difference between this comparative example and Example 1 is that hydroxypropyl cellulose is not included, and other conditions are the same.
[0121] The tensile strength and durability of this comparative example were reduced.
[0122] Test Case
[0123] The performance tests of the embodiments and comparative examples were carried out, and the results are shown in Table 1:
[0124] Concrete mechanical properties test: The concrete modules prepared in each embodiment were tested for mechanical properties in accordance with GB / T 50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete";
[0125] Test and calculate the compressive strength of concrete in accordance with Section 6 of the above standard;
[0126] Test and calculate the splitting tensile strength of concrete in accordance with Section 9 of the above standard;
[0127] Table 1 Test results
[0128]
[0129] It can be seen from the above embodiments and comparative examples that in the present invention, the introduction of the grafting agent makes the surface of the wood fiber more hydrophilic, thereby enhancing its compatibility with water-based liquids (such as concrete slurry) and improving the adhesion between the wood fiber and the concrete matrix: the wood fiber treated with grafting polymerization has better dispersibility and stability in concrete, can effectively reduce the shrinkage cracks of concrete, and improve the tensile strength and durability.
[0130] Wood fibers, through their natural fiber structure, form air bubbles in the concrete and provide structural support.
[0131] On the one hand, the carboxyl group (-COOH) on the modified wood fiber reacts with the amino group in the aminosulfonate surfactant to form an amide bond, which helps to firmly adsorb the surfactant molecules on the surface of the wood fiber to form a molecular film, which can reduce the pore size of the bubbles in the liquid and make the bubbles more stable. In concrete, it helps to reduce the pore size of the pores in the concrete, reduce the porosity in the concrete, improve the density and impermeability of the concrete, and improve the uniformity, density and durability of the concrete. On the other hand, the surface of the modified wood fiber has amino functional groups, which provide active sites to react with Ca in the cement hydration products. 2+ Ionic bonding helps promote the secondary hydration reaction of cement, which in turn promotes the hardening and strength of concrete.
[0132] Silica sol may form a silicon-oxygen cluster structure on the surface of modified wood fiber. These clusters may be combined with the surface of wood fiber through chemical bonds to form a protective layer of silicon-oxygen clusters. It can play the following roles: 1. It helps to prevent the decomposition and destruction of wood fiber in concrete, and improve its stability and durability in concrete; 2. The silicon-oxygen clusters combine with silicates on the surface of cement particles to increase the dispersibility of cement particles and promote the contact between cement particles and water; 3. The interaction between silica sol and the surface of cement particles helps to promote the secondary hydration reaction of cement and release metal ions, such as calcium ions (Ca 2+ ), chemically react with the hydrates in cement, such as calcium ions forming more CSH gel with silicates and water in cement. This helps to enhance the mechanical properties and durability of cement and improve the overall performance of concrete.
[0133] Silica sol may form silicon-oxygen cluster structures on the surface of modified wood fibers. These silicon-oxygen clusters may combine with silicates on the surface of cement particles, increase the dispersibility of cement particles, promote the contact between cement particles and water, and thus promote the secondary hydration reaction of cement. The reaction products may contain metal ions, such as calcium ions (Ca 2+ ), aluminum ions (Al3+), etc. These metal ions may react chemically with the hydrates in cement and promote the secondary hydration reaction of cement. When calcium ions react with silicates and water in cement, the generated CSH gel increases. CSH gel is one of the main components of cement hydration products, and it plays a key role in the cement hardening process. Therefore, the addition of calcium ions may promote the formation of more CSH gel, which can enhance the mechanical properties and durability of cement-based materials.
[0134] The present invention is not limited to the above-mentioned embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A high-strength all-light concrete, It is characterized in that The raw materials include, by weight: 500-540 parts of cement, 90-110 parts of mineral powder, 50-60 parts of fly ash, 300-500 parts of pottery sand, 350-380 parts of shale ceramsite and 60-70 parts of hydroxypropyl cellulose.
2. The high-strength all-light concrete according to claim 1, It is characterized in that The cement comprises P.O42.5 grade cement.
3. The high-strength all-light concrete according to claim 1, It is characterized in that The raw materials for preparing the high-strength all-light concrete also include: polycarboxylate water-reducing agent; The water reduction rate of the carboxylic acid water reducer is 25-28%.
4. The high-strength all-light concrete according to claim 1, It is characterized in that The raw materials for preparing the high-strength all-light concrete also include: aminosulfonate, modified wood fiber and silica sol; The raw materials for preparing the modified wood fiber include wood fiber, a grafting agent and an initiator.
5. The high-strength all-light concrete according to claim 4, It is characterized in that The silica sol comprises a nano-scale silica sol aqueous solution, and the particle size of the silica sol is 10-30 nm.
6. The high-strength all-light concrete according to claim 4, It is characterized in that The grafting agent includes at least one of methacrylic acid, acrylic acid, acryloyl chloride, vinylacyl chloride silane and acrylamide.
7. The high-strength all-light concrete according to claim 4, It is characterized in that The initiator includes at least one of ammonium persulfate and potassium persulfate.
8. A method for preparing the high-strength all-light concrete according to any one of claims 1 to 7, It is characterized in that The following steps are involved: The raw materials for preparing the high-strength all-light concrete are mixed, stirred and then poured.
9. The method for preparing high-strength all-light concrete according to claim 78, It is characterized in that The preparation method of the modified wood fiber comprises: mixing and reacting the wood fiber, the grafting agent and the initiator.
10. Use of the high-strength all-light concrete according to any one of claims 1 to 7 in high-rise buildings.
Citation Information
Patent Citations
Method of producing pump-transporting light aggregate concrete
CN101134346A
High toughness concrete
CN109095862A
Full-light high-strength concrete for fabricated prefabricated part and preparation method thereof
CN110922118A
Lightweight high-strength concrete as well as preparation method and application thereof
CN112266210A
Admixture for recycled aggregate concrete and preparation method thereof
CN112679132A
